Use of dupilumab on the treatment of moderate-to-severe asthma: a systematic review - Bassani,Cíntia (2019)
SUMMARY OBJECTIVE The objective of this article was to conduct a systematic review of the treatment of moderate-to-severe asthma by administrating Dupilumab. METHODS A search on the online databases EBSCO, Scielo, PubMed, Medline Bireme, Lilacs, and The New England Journal of Medicine was conducted, publications from 2010 to 2018 were selected. The inclusion criteria were articles which contained control groups, tested the validity of Dupilumab, and verified the response of patients through controlled tests. For the search of such articles, the following keywords were used: “Dupilumab”, “asthma”, “Bronchial Asthma” AND “Asthma, Bronchial” AND their correspondent in Portuguese “asma”, “Asma brônquica” and “Asma brônquica”. The exclusion criteria were literature reviews, news, articles without control groups, articles on different subjects, Dupilumab studies on other diseases, articles concerning asthma without the use of Dupilumab, and repeated articles on the databases were discarded. RESULTS The literature considers that the medication shows a good response for the treatment of moderate-to-severe asthma and assists in the improvement of lung function, aside from resulting in few side effects. It presents good efficacy, safety, and tolerance by patients. CONCLUSIONS Dupilumab is promising for the treatment of asthma, whereas conventional therapy is deemed to be insufficient. More additional studies are needed to confirm the long-term safety and effectiveness.